Production of boric acid from colemanite ore in the semi-batch reactor: Investigation of product yield and impurity control - Kaya, Fatih; Ozer, Ahmet (Pergamon-Elsevier Science Ltd, 2024)
Boric acid is produced by the reaction between colemanite ore and sulfuric acid in industrial processes. Since colemanite ore is not pure, various side reactions, including partial clay decomposition, can occur in the reactor medium. These reactions also lead to the presence of impurities, specifically sulfate salts. In this context, semibatch reactors (SBR) provide selectivity, and the rate of side reactions is reduced. However, batch reactors (BR) and continuous stirred tank reactors (CSTR) have been used for boric acid production both on an industrial scale and on a laboratory scale, and the semi-batch reactor has never been used for this area. This study used SBR to minimize the side reactions rate and impurities for boric acid production. In the experimental process, a specific concentration of sulfuric acid solution was fed to the reactor at varying flow rates. The yield in the SBR increased up to 99.6%, depending on the sulfuric acid feed rate. When the same conditions were applied in the BR experiment, the yield was calculated to be 90.8%. Compared with the batch reactor results, it was observed that the impurity concentration in the boric acid solution produced within the SBR decreased by 41.7% to 45.3%, depending on the feed rate. Consequently, the utilization of SBR demonstrated clear advantages over the BR in terms of both yield and impurity control. Furthermore, this study serves as a compelling illustration of the practical applications of solid-liquid heterogeneous phase reactions within the context of SBR technology.
Keywords: Boric acid production; Semi-batch reactor; Impurity control; Sulfate impurity; Solid-liquid heterogeneous phase reaction